An Approach to Manage Shweta Pradar – A Case Study - Srivastava, Pragati; Singh, Shashi (International Research Journal of Ayurveda & Yoga, 2022)
Acharya Manu has said that happiness of human needs proper care and respect of woman. So, to keep our society happy and healthy, proper care of woman is the most important thing. Shweta Pradar is one of the most common problems faced by woman in her day-to-day life. Slight discharges through vagina occur physiologically to keep the vagina moist but if discharges increase in amount or it comes with foul smell or with itching, it causes discomfort to the patient. Medications which are being used to treat Leucorrhea are unable in controlling its reoccurrence. Ayurvedic medications and localized procedures (Sthanik Chikitsa) have been proved like a boon in this field. Here, a case report of a female patient having complaints of thick white discharge P/V, burning in vaginal area, burning micturition, low back ache and constipation has been presented. She was advised for sthanik chikitsa. After taking patient’s consent, Yoni Prakshalana (vaginal wash) with Udumbaradi Kashaya and Yoni Pichu (vaginal tampon) with Udumbaradi Taila was done for 7 days after the cessation of menstrual flow. The procedure was done for the 3 consecutive cycles & the patient started feeling relief in symptoms from the very first cycle. Thus, through this study, the efforts have been done to through light on the importance of shtanik chiktsa in the field of Stri Roga (gynecological disorders).